La notion de prochain dans les premiers écrits d’Augustin. Esquisse de réflexion - Lagouanère, Jérôme (Revue d'études augustiniennes et patristiques, 2011)
Augustinian notion of neighbour has not been often studied, although it is very important to understand his thought. In this article, we will try to study how and why Augustine’s point of view has changed about it. We will first examine how he deals with this notion for the first time in the De moribus ecclesiae catholicae; then, how he interprets the parable of the Good Samaritan in later works. Thus, we will show that his way of defining the notion of neighbour evolved a lot, because it is first infl uenced by the pagan notion of iustitia and, then, it became a christologic concept thanks to the infl uence of Ambrose’s and, mainly, Origene’s interpretations of the Bible.